From Zero To Hero In The Blind Side Movie (2009) By john Lee Hancock : An Individual Psychological Approach - NURWIYANTI, FITRI (2012)
This research paper is aimed to show How Michael Oher's struggle as major character is reflected in The Blind Side movie. Therefore, the study analyses the movie in terms of its structural elements and based on the individual psychological analysis. The writer uses qualitative study, in which the primary data is the movie of The Blind Side directed by John Lee Hancock released in 2009, and secondary data is the other data related to the research such as some books of individual psychological theory by Alfred Adler, movie script, commentaries, internet, and other relevant information. The method of data collection is library research. The technique of data analysis is descriptive analysis. Results of the analysis are as follows: Firstly, the structural elements of the movie present a solid unity. Secondly, the individual psychological analysis shows that of Michael Oher's struggle influences his personality in facing social life. He feels there is no one who is kind to him and he is alone because he is homeless teenager and big body African American. Those problems produce weak feeling that affects his personality. His weakness in social sphere drives him to overcome his inferiority. He compensates his weaknesses by striving to get his goal of life. Finally, he can live happily, peacefully with the new family and also he becomes a hero as professional football player.